Improvement Of Inactivated Equine Herpes Virus-1 Vaccine Using Carbomer - Safaa, A. Warda (Egyptian Society for Animal Management, 2021)
An inactivated Equine herpes virus-1 vaccine was successfully improved using carbomer as adjuvant inducing high and long immunity in vaccinated mares in comparison with the convention one adjuvanted with Al-hydra gel and saponin. Such purpose was established by using 0.5% carbomer as adjuvant to the inactivated EHV-1. The applied quality control tests carried out on such vaccine revealed that it is free from foreign contaminants, safe in pregnant mares and mice and potent induced high levels of specific EHV-1 antibodies in vaccinated Guinea pigs and mares as measure by ELISA and SNT. This immunity was sufficient to protect vaccinated horses up to 28 weeks (7months) post-vaccination.